2021
DOI: 10.1016/j.jneb.2021.04.433
|View full text |Cite
|
Sign up to set email alerts
|

P41 Yumbox: Bringing MyPlate to Preschoolers' Lunches

Abstract: Objective: To test whether Yumbox, a bento-style lunchbox with compartments labeled for the 5 meal components of USDA's MyPlate, has an effect on foods that caregivers packed for preschoolers' lunches. Use of Theory: Yumbox provides distinct compartments for recommended food components of USDA MyPlate, leveraging visibility principals of behavioral economics theory. Caregivers may be more likely to pack lunches that include more components of MyPlate due to visual cues present in Yumbox. Target Audience: Careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A total of 23 intervention studies were identified from the 22 peer-reviewed articles. Nine were randomised controlled trials (RCTs) (two with low [41,42] and seven with high risk of bias [43][44][45][46][47][48]), seven were quasi-experimental studies (three with low [49][50][51] and four with high risk of bias [52][53][54][55]), five were cross-sectional studies (one with low [56] and four with high risk of bias [57][58][59][60]), and two were qualitative studies with a high risk of bias [61,62].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 23 intervention studies were identified from the 22 peer-reviewed articles. Nine were randomised controlled trials (RCTs) (two with low [41,42] and seven with high risk of bias [43][44][45][46][47][48]), seven were quasi-experimental studies (three with low [49][50][51] and four with high risk of bias [52][53][54][55]), five were cross-sectional studies (one with low [56] and four with high risk of bias [57][58][59][60]), and two were qualitative studies with a high risk of bias [61,62].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 intervention studies, 16 studies were conducted with adults [41][42][43][44]46,[48][49][50]52,53,56,[58][59][60][61] and 7 were conducted with children and adolescents [45,47,51,54,55,57,62]. The effect of the portion control plate was examined using 2D plate diagrams (n = 12) [44,49,50,52,53,[55][56][57][58][59][60]62] and using 3D portion plates (n = 11) [41][42][43][45][46][47][48]51,54,61]. An overview of eight types of portion control plates found in the grey literature is provided in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations